2022
DOI: 10.3390/ijms23179732
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence Analysis of Bacillus subtilis Bbv57, a Promising Biocontrol Agent against Phytopathogens

Abstract: Plant growth-promoting rhizobacteria (PGPR) are a group of root-associated beneficial bacteria emerging as one of the powerful agents in sustainable plant disease management. Among the PGPR, Bacillus sp. has become a popular biocontrol agent for controlling pests and the diseases of several crops of agricultural and horticultural importance. Understanding the molecular basis of the plant growth-promoting and biocontrol abilities of Bacillus spp. will allow us to develop multifunctional microbial consortia for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Cellulase, a cell wall-degrading enzyme, can affect the structural integrity of the host plants, thereby indirectly promoting host plant growth, suggesting a role for bacteria of the genus Saccharibacillus in plant growth and/or biocontrol. This finding is significant in light of the increasing applications being identified for biofertilizers in modern agriculture (e.g., the GRAS Bacillus strain) (Chen et al 2019 ; Majeed et al 2018 ; Bhardwaj et al 2014 ; Zaid et al 2022 ; Zhao et al 2022 ; Thiruvengadam et al 2022 ). In the present study, we found that the strain ATSA2 T , which is an endophyte of kimchi cabbage, contains no antibiotic resistance genes or virulence genes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Cellulase, a cell wall-degrading enzyme, can affect the structural integrity of the host plants, thereby indirectly promoting host plant growth, suggesting a role for bacteria of the genus Saccharibacillus in plant growth and/or biocontrol. This finding is significant in light of the increasing applications being identified for biofertilizers in modern agriculture (e.g., the GRAS Bacillus strain) (Chen et al 2019 ; Majeed et al 2018 ; Bhardwaj et al 2014 ; Zaid et al 2022 ; Zhao et al 2022 ; Thiruvengadam et al 2022 ). In the present study, we found that the strain ATSA2 T , which is an endophyte of kimchi cabbage, contains no antibiotic resistance genes or virulence genes.…”
Section: Discussionmentioning
confidence: 91%
“…These bacteria may contribute to plant growth and health by assisting in nutrient uptake or by suppressing plant pathogens (Vejan et al 2016 ; Afzal et al 2019 ; Saberi Riseh et al 2021 ; Majeed et al 2018 ; Bhardwaj et al 2014 ; Nanjani et al 2022 ). Many studies have demonstrated plant–microbe symbiosis, in which bacteria produce extracellular enzymes or metabolites, thereby improving mineral nutrition and thus impacting plant health and growth, while plants provide energy to those beneficial microbes (Marschner and Rengel 2007 ; Santoyo et al 2016 ; Hardoim et al 2008 ; Zhao et al 2022 ; Thiruvengadam et al 2022 ). Rhizospheric and endophytic bacteria, which are cost-effective and environmentally friendly, have been widely used in biological control methods and plant biofertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Except for surfactin, all other peptides, including subtilomycin, bacillaene, fengycin, bacillibactin, subtilosin, and bacilysin were identified as 100% in contig 2; these peptides play a role in the suppression of pathogens by inducing systemic resistance ( Kamali et al, 2022 ). In a recent report by Thiruvengadam et al (2022) , genomic analysis of the strain B. subtilis Bbv57 isolated from betelvine rhizosphere sediments revealed 9 putative biosynthetic secondary metabolite gene clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the CAZyme analysis provided insight into the enzymatic landscape of the bacteria present in honey. Thiruvengadam et al ( 2022 ) isolated B. subtilis Bbv57 from the betel vine rhizosphere and found glycosyl transferases and glycoside hydrolases present predominantly in the genome. Endo β 1, 4 glucanase, chitinase, endoglucanase, and xyloglucanase were also detected in their study (Thiruvengadam et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thiruvengadam et al ( 2022 ) isolated B. subtilis Bbv57 from the betel vine rhizosphere and found glycosyl transferases and glycoside hydrolases present predominantly in the genome. Endo β 1, 4 glucanase, chitinase, endoglucanase, and xyloglucanase were also detected in their study (Thiruvengadam et al 2022 ). In another study, Chen et al ( 2022 ) isolated B. subtilis CTXW 7–6-2 from kiwi fruit and observed the same results.…”
Section: Discussionmentioning
confidence: 99%